A retrospective study on post-operative hearing of middle ear cholesteatoma patients with labyrinthine fistula. (2nd January 2016) - Bo, Yue; Yang, Yang; Xiaodong, Chen; Xi, Wang; Keyong, Tian; Yu, Zhao; Ye, Wang; Kun, Liang; Zheng, Yang; Yang, Chen; Jianhua, Qiu
Abstract: Conclusions : There is no significant change in bone conduction threshold after operation, so the tympanoplasty can be done to maintain hearing when conditions allow. Objective : To study the impact of surgical treatment on hearing of cholesteatoma patients with labyrinthine fistula. Methods : The clinical data of 35 patients (35 ears) with labyrinthine fistula, which were caused by cholesteatoma, were analyzed retrospectively. The hearing of 21 patients was followed up. Results : Three months to 5 years follow-up of 21 patients were accomplished by pure tone audiometry and other details. There was no recurrent cholesteatoma in the patients. Compared with pre-operative average bone conduction at 0.5, 1, 2, 4, and 8 kHz, 12 cases had a difference less than 5 dB, three patients' hearing improved (more than 10 dB), and five cases declined (more than 10 dB). One patient received cochlear implantation 3 months after the surgery. The average bone and air conduction thresholds at 0.5, 1, 2, 4, and 8 kHz had no obvious change ( p > 0.05) in 11 patients managed by a canal wall down mastoidectomy with tympanoplasty.